1984
DOI: 10.1177/073428298400200304
|View full text |Cite
|
Sign up to set email alerts
|

The Luria-Nebraska Neuropsychological Battery-Children's Revision: Validation with Brain-Damaged and Normal Children

Abstract: This paper discusses briefly the development and rationale behind the Luria-Nebraska Neuropsychological Battery-Children's Revision. Three investigations are discussed: (a) the development of normative data on a group of 125 normal children between the ages of 96 and 155 months, (b) development of the critical level formula for determining the upper bounds for normal performance given a child's age, and (c) a validation of the ability of the battery to discriminate between normal and brain-injured children sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…In a discriminant function analysis, the Pathognomonic scale contributed the most for predicting membership for two separate clinical groups: Group 1 was comprised of 125 normals and 76 brain-impaired, and Group 2 was comprised of 91 normals and 58 brainimpaired children (Sawicki et al, 1984). The overall classification rates were higher than previously reported by Wilkening et al (1981) and by Gustavson et al (1981). When the Pathognomonic and the Left Sensorimotor scales wee added to the 11 original scales, the following hit rates were reported: 96.7% for normals and 88.9% for brain-injured in Group 1 and 95.6% for normals and 79.3% for brain-injured in Group 2 (Sawicki et al, 1984).…”
contrasting
confidence: 70%
See 4 more Smart Citations
“…In a discriminant function analysis, the Pathognomonic scale contributed the most for predicting membership for two separate clinical groups: Group 1 was comprised of 125 normals and 76 brain-impaired, and Group 2 was comprised of 91 normals and 58 brainimpaired children (Sawicki et al, 1984). The overall classification rates were higher than previously reported by Wilkening et al (1981) and by Gustavson et al (1981). When the Pathognomonic and the Left Sensorimotor scales wee added to the 11 original scales, the following hit rates were reported: 96.7% for normals and 88.9% for brain-injured in Group 1 and 95.6% for normals and 79.3% for brain-injured in Group 2 (Sawicki et al, 1984).…”
contrasting
confidence: 70%
“…In a cross-validation study, Gustavson et al (1981) found slightly higher accuracy rates with 91 normals and 58 brain-damaged children. Overall classification accuracy for these groups reached 85%.…”
mentioning
confidence: 83%
See 3 more Smart Citations